Personal information searching and identification in personal computer - Jaafar, Noorasheila (2013)
Personal computer (PC) is a microprocessor designed for an individual user. Over few decades, personal computer has evolved into high power machine which plays huge role in our daily lives, both for work and play. We use personal computer for communication, internet browsing, online transaction and social networking. We create files and emails and during all these activities, our PC collects information. After years of use, in all these exchange a notable amount of personal information and sensitive data are stored within our PC. Personal information is detail used to distinguish and identify an individual. The personal information stored within PC is not used regularly by user and is in fact can be considered as a liability. Disclosure of personal information exposed users to the risk of being a victim to hackers. Hence, user should regularly check the information gathered within PC and clean any unnecessary personal information. This research examined on categories of personal information commonly found on personal computer. A technique was proposed which helps user to search the existence and identify the location of personal information in the PC. The collected data from the technique is then analyzed. The proposed technique was also tested and some future works are suggested at the end of this study.